Innate immunity and effector and regulatory mechanisms involved in allergic contact dermatitis - Marilene Chaves Silvestre; Maria Notomi Sato; Vitor Manoel Silva dos Reis (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Skin's innate immunity is the initial activator of immune response mechanisms, influencing the development of adaptive immunity. Some contact allergens are detected by Toll-like receptors (TLRs) and inflammasome NLR3. Keratinocytes participate in innate immunity and, in addition to functioning as an anatomical barrier, secrete cytokines, such as TNF, IL-1β, and IL-18, contributing to the development of Allergic Contact Dermatitis. Dendritic cells recognize and process antigenic peptides into T cells. Neutrophils cause pro-inflammatory reactions, mast cells induce migration/maturation of skin DCs, the natural killer cells have natural cytotoxic capacity, the γδ T cells favor contact with hapten during the sensitization phase, and the innate lymphoid cells act in the early stages by secreting cytokines, as well as act in inflammation and tissue homeostasis. The antigen-specific inflammation is mediated by T cells, and each subtype of T cells (Th1/Tc1, Th2/Tc2, and Th17/Tc17) activates resident skin cells, thus contributing to inflammation. Skin's regulatory T cells have a strong ability to inhibit the proliferation of hapten-specific T cells, acting at the end of the Allergic Contact Dermatitis response and in the control of systemic immune responses. In this review, we report how cutaneous innate immunity is the first line of defense and focus its role in the activation of the adaptive immune response, with effector response induction and its regulation.